2003
DOI: 10.1063/1.1512773
|View full text |Cite
|
Sign up to set email alerts
|

Ultratraces of carotenes in tomato purées: HPLC-TLS study

Abstract: The present study was designed to provide information about ͑i͒ the profile of carotene pigments and ͑ii͒ trace quantities of lycopene and ␤-carotene left in tomato purées. The ultrasensitive method comprising HPLC and thermal lens spectrometric ͑TLS͒ detection enabled us to detect as low as 0.3 and 1.1 ng ml Ϫ1 lycopene and ␤-carotene in purée extracts, respectively. Total concentration of ␤-carotene and lycopene ͑varying from 3 to 170 ng g Ϫ1 ) in the examined tomato purées may serve as an indicator of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The relatively high IR background absorption of the mobile phases used in our experiments precludes, at least for the time being, NARP-HPLC-TLS and Ag-HPLC-TLS detectors from achieving spectacular sensitivities already obtained with the same technique in the visible region when quantifying trans-beta-carotene in human blood serum [29] and fish oil based supplementary drugs, [30] detecting carotenoids in the edible oils [31] and determining the content of lycopene in tomato purees. [32] A more judicious selection of the mobile phase could compensate for this effect; however, the choice of weakly absorbing and polar eluents that are also capable of achieving good chromatographic separation may be limited. [33] …”
Section: Resultsmentioning
confidence: 99%
“…The relatively high IR background absorption of the mobile phases used in our experiments precludes, at least for the time being, NARP-HPLC-TLS and Ag-HPLC-TLS detectors from achieving spectacular sensitivities already obtained with the same technique in the visible region when quantifying trans-beta-carotene in human blood serum [29] and fish oil based supplementary drugs, [30] detecting carotenoids in the edible oils [31] and determining the content of lycopene in tomato purees. [32] A more judicious selection of the mobile phase could compensate for this effect; however, the choice of weakly absorbing and polar eluents that are also capable of achieving good chromatographic separation may be limited. [33] …”
Section: Resultsmentioning
confidence: 99%
“…By combining coaxial DBTLS with a reverse phase HPLC system, it was possible to detect as little as 0.3 and 1.1 ng/ml lycopene and beta-carotene, respectively, in extracts of tomato purees [32]. The total concentration of beta-carotene and lycopene (varying from 3 to 170 ng/g) in the investigated purees can be regarded as indicative for the assessment of carotene-specific antioxidative capacity.…”
Section: Dual Beam Thermal Lens Spectrometry (Dbtls)mentioning
confidence: 99%
“…Likewise, Luterotti et al 19 recently studied lycopene in tomato purées and reported a good correlation (R 2 = 0.85) between data acquired by conventional spectrophotometry and those obtained by HPLC combined with thermal lens spectrometry as a novel methodology to measure the absorbance.…”
Section: Introductionmentioning
confidence: 99%